Relation of polymorphisms VEGF (+405G>C) and TNFα (-308A>G) with the embryo implantation in Cubans patient undergoing in vitro fertilization - Sotomayor Lugo, Francisco; Marcheco Teruel, Beatriz; Rodríguez Martínez, Kenia; Esperón Álvarez, Alejandro; Menocal Alayón, Ahmed; Almaguer Almaguer, José Alberto; López Reyes, Ixchel; Flores Sánchez, Rosa María; Crespo Ferrán, Yoandra; Veiga Loyola, Vivian (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction. A cohort study was carried out at the National Center for Medical Genetics, from July 2017 to June 2018, in 27 patients evaluated in the consultation for the infertile couple at the Hermanos Ameijeiras Hospital. Objective. To establish the relationship of the individual and combined expression of the genotypes of the polymorphisms VEGF (+405 G> C) and TNFα (-308A> G), with the rates of embryo implantation in Cuban patients receiving treatment with in vitro fertilization. Materials and Methods.The identification of the genotypes was carried out using an ARMS PCR. The Hardy-Weinberg equilibrium was determined by applying the Chi square test of goodness of fit from a reference population, and a Principal Component Analysis (PCA) was carried out to evaluate the genotypic population structure with respect to the variables studied. Results. Individuals with combined genotype variant VEGF.CC / TNFα.GG were grouped homogeneously in the PCA model with respect to axis 2, where there was a higher frequency of women with a low implantation rate. In contrast, patients with a genotypic TNFα.AG variant were grouped according to the highest implantation rates. Conclusions. It was concluded that there is a relationship between genotype variants VEGF.CC and TNFα.GG with a low implantation rate, when they are expressed individually or in combination in patients treated with the in vitro fertilization technique, while the individual genotypic variant TNFα. AG is associated with a higher implantation rate.